The Future of Education in Turkey's 2023 Educational Vision Document: Views of Academicians in the Faculty of Education - Semerci, Çetin; Hatipoglu, Cenk; Guneri, Birsen; Sevimbay, Aziz; Akcaalan, Mumine; Cengiz Demir, Yasemin; Semerci, Çetin (Ani Yayincilik, 2020)
Purpose: This study was conducted to reveal the views of academicians, working in the Faculty of Education, on the 2023 Vision Document of the Ministry of National Education. Method: Qualitative research method was used in this study. The study group consisted of six faculty members. In the determination of participants, easily accessible situation sampling, which is one of the purposive sampling methods, was used. A descriptive qualitative research design was used in this study; interview technique and semi-structured interview form were used as data collection tools. Findings: The findings showed that the views of academicians, who participated in this study, about the education system were based on a philosophical foundation that continues from individuality to sociality, from material dimension to spiritual dimension, and emphasizes an original national and spiritual thought system extending from local to universal. Also, results indicated that, firstly, students should gain national and universal values and then should be equipped with 21st-century skills and competencies if the courses are satisfactory concerning quality, the reduction of the course hours can be positive; emphasis can be given on the necessity of giving the pedagogical formation education rather than giving it. Implications for Research and Practice: The findings obtained from this study suggest that the views of the academicians may contribute to the successful implementation of the document. Studies should be carried out to reveal the opinions of teachers and school administrators, which are important components of education programs, within the framework of the document. (C) 2020 Ani Publishing Ltd. All rights reserved
The Future of Education in Turkey’s 2023 Educational Vision Document: Views of Academicians in the Faculty of Education
Keywords: The Ministry Of National Education; Turkey's 2023 Educational Vision Document; Views Of Academicians